The Design and Characteristics of School Improvement Plan Templates - Bryan A. VanGronigen; Coby V. Meyers; Rachel Antwi Adjei; Latrice Marianno; Linda Charris (SAGE Publishing, 2023)
Resources for school improvement efforts, such as school improvement plan (SIP) templates, can espouse governmental entities' perspectives on and requirements and recommendations for the school improvement planning process. These resources, in turn, can influence how educators enact school improvement efforts generally and the school improvement planning process specifically. In this exploratory qualitative study, we leveraged a conventional content analysis to rigorously examine SIP templates used by schools in the United States before and after the passage of the Every Student Succeeds Act (ESSA) in 2015. We were particularly interested in learning how a sample of SIP templates espoused the school improvement planning process before and after ESSA's passage. Findings suggest that SIP templates focused more on developing SIPs than implementing SIPs, raising concerns about SIPs continuing to be enacted out of compliance rather than as a mechanism for spurring and sustaining improvement efforts in schools.